AI-Based World Immersed in Scholarly Communications: Paradigmatic and Theoretical Perspectives - Adakawa, Murtala Ismail; Balachandran, Chikku; Harinarayana, N. S. (Journal of Information and Knowledge, 2024)
This paper explores AI’s role in scholarly communication from different perspectives. It begins by examining how universities contributed to the development of AI and integrated it into teaching, learning, and research. As the digital economy grows, AI is influencing many aspects of human life. Different countries and funding agencies use various approaches that affect how research grants are allocated globally. AI’s use in scholarly writing is changing traditional communication methods. Although little research exists on the impact of AI-generated writing on metrics like the h-index, this paper discusses several issues from different perspectives. It aims to provide insights to AI researchers to improve the technology for better outcomes.